In vitro bioaccessibility of intrinsically zinc-enriched egg and effect of cooking - Hatairat Plaimast (2018)
Adequate dietary zinc is essential for appropriate growth, neurological development, and immune function in all age groups, especially in children. Eggs are a potentially attractive means of delivering dietary zinc. This study used an in vitro continuous-flow dialysis (CFD) method to determine the effect of cooking (boiling or frying) on bioaccessibility of zinc from eggs which had been biofortified in vivo. The intrinsically zinc-enriched eggs with the highest level of zinc (18 μg/g) provided the highest available zinc at 75%. There was no statistically significant difference in the bioaccessibility of zinc from eggs enriched with inorganic zinc versus enrichment with organic zinc. The intrinsically zinc-enriched eggs from hens fed both organic and inorganic forms with the maximum available zinc (about 13.5 μg zinc/g) were selected to study the effect of cooking. Boiling and frying did not have any adverse effect on zinc bioaccessibility in the eggs intrinsically enriched with inorganic zinc. However, boiling reduced by about 6% and frying reduced by about 10% the bioaccessible zinc in the control and eggs intrinsically enriched with organic zinc. One intrinsically enriched egg could provide 142% of the daily zinc requirement for a child aged one year. © 2009 Elsevier Inc. All rights reserved.